2020
DOI: 10.3390/cells9092013
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Oxidative Phosphorylation Reverses Drug Resistance in Cancer Cells by Blocking Autophagy Recycling

Abstract: The greatest challenge in cancer therapy is posed by drug-resistant recurrence following treatment. Anticancer chemotherapy is largely focused on targeting the rapid proliferation and biosynthesis of cancer cells. This strategy has the potential to trigger autophagy, enabling cancer cell survival through the recycling of molecules and energy essential for biosynthesis, leading to drug resistance. Autophagy recycling contributes amino acids and ATP to restore mTOR complex 1 (mTORC1) activity, which leads to cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…Mechanistically, it has been proposed that glutamine-fueled OXPHOS represents an essential source of energy for the proliferation of drug-resistant tumor cells and, accordingly, blockade of OXPHOS with an inhibitor of complex I of the electron transport chain overcame the drug resistance [169] . Very recently, it has been shown that OXPHOS blockade through complex I inhibition leads to inhibition of the autophagic process that was induced by drug treatment and led to tumor cell survival and drug resistance [170] .…”
Section: Conclusion and Perspectives—from Glycolysis- To Oxphos-assomentioning
confidence: 99%
“…Mechanistically, it has been proposed that glutamine-fueled OXPHOS represents an essential source of energy for the proliferation of drug-resistant tumor cells and, accordingly, blockade of OXPHOS with an inhibitor of complex I of the electron transport chain overcame the drug resistance [169] . Very recently, it has been shown that OXPHOS blockade through complex I inhibition leads to inhibition of the autophagic process that was induced by drug treatment and led to tumor cell survival and drug resistance [170] .…”
Section: Conclusion and Perspectives—from Glycolysis- To Oxphos-assomentioning
confidence: 99%
“…Although, several mechanisms for the development of drug resistance in the tumor have been identified, the general approaches for over-coming tumor drug-resistance focus on either inhibiting molecular events underlying resistance or using particulate carrier systems for increasing the drug accumulation at the target site [21][22][23][24][25][26][27]. Recent advances in understanding the cellular metabolism of drug resistant tumor cells, suggest that contrary to the prevailing Warburg theory that tumor cells rely on aerobic glycolysis, certain drug-resistant tumor cells in fact rely on increased OXPHOS activity for their survival [4,11,12,[28][29][30]. These recent findings offered a new insight to previous studies [5] in which STPP appeared to have a greater level of toxicity toward drug resistant ovarian carcinoma Ovcar-3 tumor cells compared to non-drug resistant ovarian carcinoma A2780 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced, accelerated aerobic glycolysis has been shown to be responsible for resistance against various cancer drugs including sorafenib [ 529 ], palbociclib [ 530 ], oxaliplatin [ 531 ], doxorubicin [ 532 ], lapatinib [ 533 ] paclitaxel [ 534 ], bevacizumab [ 535 ], and cetuximab [ 536 ]. However, recent studies also revealed that many cancers such as myeloid leukemia [ 537 ], non-Hodgkin’s lymphoma [ 538 ], pancreatic ductal adenocarcinoma [ 539 ], melanoma [ 540 ], and high-grade prostate cancers [ 541 ] do not have impaired mitochondrial OXPHOS [ 542 ] while aggressive and drug-resistant cancers may actually upregulate mitochondrial oxidative phosphorylation (OXPHOS) as part of their defense mechanisms [ 543 , 544 , 545 ] to enhance autophagy [ 546 ], increase stemness [ 547 ], or remodel OXPHOS metabolism to promote survival [ 541 , 548 ].…”
Section: Melatonin May Promote Prp Physiological Functions and Inhibi...mentioning
confidence: 99%